Low reflection electromagnetic shielding film with asymmetric gradient and method of manufacturing the same
Patent Information
- Application Number
- CN202611059183.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明的目的在于提供一种具有非对称梯度的低反射电磁屏蔽薄膜及其制备方法,用以解决现有的电磁屏蔽材料存在高屏蔽与低反射难以兼顾的技术问题
本发明公开了一种具有非对称梯度的低反射电磁屏蔽薄膜的制备方法,该方法将C-Co、LM与Ti3C2TXMXene在BC骨架中进行分层自组装,实现了非对称电磁双梯度结构的构建;其中,顶层富集磁性C-Co优化了阻抗匹配,促使电磁波进入薄膜内部;中间层协同LM与C-Co,实现电磁波的介电与磁双重耗散;底层富集Ti3C2TXMXene与LM构筑强反射屏障,诱导电磁波发生“吸收-反射-再吸收”过程,使薄膜在X波段实现63.65 dB的优异屏蔽效能的同时,将反射效能降至8.05 dB,有效防止了二次电磁污染;此外,引入BC作为贯穿三层的柔性骨架,结合LM的流体特性,使复合薄膜具备35.47 MPa的高拉伸强度;同时底层高导电网络与顶层多孔碳结构赋予了薄膜双模态热管理功能,不仅具备低压驱动的快速焦耳加热性能(2.5 V下表面温度达121.9 ℃),还具备高效的光热转换能力(30s内2 Sun光照下表面温度达80 ℃)。
Smart Images

Figure CN122875738A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic shielding film technology, specifically relating to a low-reflection electromagnetic shielding film with an asymmetric gradient and its preparation method. Background Technology
[0002] With the increasing integration and high frequency of modern electronic devices, electromagnetic interference problems are becoming increasingly serious, making the development of high-performance electromagnetic shielding materials an urgent priority. Highly conductive materials, such as MXene, exhibit extremely high electromagnetic shielding effectiveness due to their excellent carrier migration capabilities. However, their ultra-high conductivity inevitably leads to a severe impedance mismatch between the material and free space, causing most incident electromagnetic waves to be directly reflected at the material surface, resulting in serious secondary electromagnetic radiation pollution.
[0003] To address the high reflection problem, existing technologies typically introduce magnetic or dielectric loss components to adjust impedance matching. However, Zhou et al. (Meng Zhou, Zan Yu, Qiming Yan, Xinya Zhang. Asymmetric Structural Design for Absorption‐Dominated Electromagnetic Interference Shielding Composites, Advanced Functional Materials, 2025, Vol. 35, Article No. 2423884) pointed out in their research on absorption-dominant electromagnetic shielding materials that existing shielding materials mostly employ homogeneous blend structures, making it difficult to overcome the contradiction between "impedance matching" and "conductive shielding": while introducing loss components can reduce reflection, it easily disrupts the continuous conductive network, leading to a decrease in shielding effectiveness; maintaining high conductivity inevitably results in severe reflection. Therefore, how to achieve path control of electromagnetic waves—"easy incidence-high dissipation-strong blocking"—through precise spatial structure design, fundamentally overcoming the difficulty of simultaneously achieving high shielding and low reflection, is a major challenge currently facing electromagnetic shielding structure design. Summary of the Invention
[0004] The purpose of this invention is to provide a low-reflection electromagnetic shielding film with an asymmetric gradient and its preparation method, so as to solve the technical problem that existing electromagnetic shielding materials cannot simultaneously achieve high shielding and low reflection.
[0005] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient, comprising the following steps: S1: Carbon-coated cobalt nanospheres were added to the bacterial cellulose dispersion and stirred to obtain the top layer dispersion; S2: Liquid metal suspension and carbon-coated cobalt nanospheres are added to bacterial cellulose dispersion and stirred to obtain intermediate layer dispersion; S3: Ti3C2T X MXene dispersion and liquid metal suspension were added sequentially to bacterial cellulose dispersion, and the mixture was stirred to obtain the bottom dispersion. S4: The top layer dispersion, the middle layer dispersion and the bottom layer dispersion are sequentially filtered to form a film, and the top layer film, the middle layer film and the bottom layer film are obtained in sequence; the top layer film, the middle layer film and the bottom layer film are sequentially stacked, dried and hot-pressed to obtain a low-reflection electromagnetic shielding film with an asymmetric gradient.
[0006] Furthermore, in S1, the preparation process of the carbon-coated cobalt nanospheres is as follows: Dissolve 2-10 mmol adenine in 80-400 mL N,N-dimethylformamide, heat to 140 °C, and then add dropwise 20-100 mL N,N-dimethylformamide solution containing 1-5 mmol cobalt nitrate hexahydrate. After reacting for 4 h, a precursor is obtained. The precursor is then carbonized at 600 °C for 1-2 h under an argon atmosphere to obtain carbon-coated cobalt nanospheres. The preparation process of the top layer dispersion is as follows: Add 0.08~0.12g of the carbon-coated cobalt nanospheres to 50 mL of bacterial cellulose dispersion with a concentration of 1 mg / mL, sonicate for 30 min and stir for 2~3 h to obtain the top layer dispersion.
[0007] Furthermore, in S2 and S3, the preparation process of the liquid metal suspension is as follows: Add 0.1~0.5g of eutectic gallium-indium alloy to 10~50mL of anhydrous ethanol and ultrasonically disperse for 1h~2h. Centrifuge and redisperse the precipitate in deionized water to prepare a liquid metal suspension with a concentration of 5mg / mL.
[0008] Furthermore, in S2, the ratio of the C-Co nanospheres to the liquid metal suspension is 0.04~0.06g:8~12mL; The specific preparation process of the intermediate layer dispersion is as follows: C-Co nanospheres and a liquid metal suspension with a concentration of 5 mg / mL were added to 40 mL of bacterial cellulose dispersion with a concentration of 1 mg / mL. The mixture was sonicated for 30 min and stirred for 2-3 h to obtain an intermediate layer dispersion.
[0009] Furthermore, in S3, Ti3C2T X The preparation method of MXene dispersion is as follows: Dissolve 1-2 g of lithium fluoride in 20-40 mL of 9 mol / L hydrochloric acid solution, then add 1-2 g of Ti3AlC2 powder and stir at 30-40 °C for 24-36 h for etching. Wash the resulting product repeatedly with deionized water and centrifuge until the pH of the supernatant is approximately 6. Collect the precipitate and sonicate it for 1-1.5 h, then centrifuge at 3600-4500 rpm for 0.5-1 h. Take the supernatant to obtain Ti3C2T. X MXene dispersion.
[0010] Furthermore, in S3, the method for preparing the bottom dispersion is as follows: Ti3C2T X MXene dispersion and a liquid metal suspension with a concentration of 5 mg / mL were added sequentially to 30 mL of bacterial cellulose dispersion with a concentration of 1 mg / mL. After stirring for 2-3 h, the mixture was sonicated in an ice bath for 30 min to obtain the bottom dispersion.
[0011] Furthermore, in S3, the Ti3C2T in the bottom dispersion X The ratio of MXene to liquid metal suspension is 0.012~0.06g: 20~24mL.
[0012] Further, in S1~S3, the preparation process of the bacterial cellulose dispersion is as follows: dissolve bacterial cellulose in deionized water and stir thoroughly for 1~2 hours to obtain the bacterial cellulose dispersion.
[0013] Furthermore, the mass ratio of carbon-coated cobalt nanospheres in the top layer dispersion to carbon-coated cobalt nanospheres in the middle layer dispersion is 2:1; In S3, the filtration membrane formation is performed using vacuum-assisted filtration; the filter membrane used in the vacuum-assisted filtration is a polytetrafluoroethylene microporous filter membrane; the drying is vacuum drying, the temperature of the vacuum drying is 40~60℃, and the time is 4~8h; the hot pressing temperature is 40℃, the pressure is 5kPa, and the time is 0.5~1h.
[0014] This invention also discloses a low-reflection electromagnetic shielding film with an asymmetric gradient. The asymmetric gradient of the low-reflection electromagnetic shielding film is as follows: in the thickness direction of the film, from the top layer to the bottom layer, the content of the magnetic component carbon-coated cobalt nanospheres gradually decreases, while the content of the conductive component Ti3C2T... X The content of MXene and liquid metal gradually increases, forming a functional gradient distribution with the top layer dominated by magnetic loss, the middle layer having both magnetic and dielectric loss, and the bottom layer dominated by dielectric loss.
[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient, wherein C-Co, LM and Ti3C2T are mixed. X MXene performs layered self-assembly within a BC framework, enabling the construction of an asymmetric electromagnetic dual-gradient structure. The top layer, enriched with magnetic C-Co, optimizes impedance matching, facilitating electromagnetic wave penetration into the film. The middle layer, in conjunction with LM and C-Co, achieves both dielectric and magnetic dissipation of electromagnetic waves. The bottom layer is enriched with Ti3C2T. X MXene and LM form a strong reflection barrier, inducing an "absorption-reflection-reabsorption" process for electromagnetic waves. This enables the film to achieve an excellent shielding efficiency of 63.65 dB in the X-band while reducing the reflection efficiency to 8.05 dB, effectively preventing secondary electromagnetic pollution. In addition, BC is introduced as a flexible skeleton that runs through the three layers. Combined with the fluid properties of LM, the composite film has a high tensile strength of 35.47 MPa. At the same time, the highly conductive network at the bottom layer and the porous carbon structure at the top layer endow the film with dual-mode thermal management function. It not only has the rapid Joule heating performance driven by low voltage (the surface temperature reaches 121.9 ℃ at 2.5 V), but also has the efficient photothermal conversion capability (the surface temperature reaches 80 ℃ under 2 Suns illumination within 30s). Attached Figure Description
[0016] Figure 1 The diagram shows the structure, cross-sectional scanning electron microscope (SEM) image, and EDS elemental mapping image of the G-BC / MXene / LM / C-Co thin film prepared in Example 1 of this invention. Among them, a-a schematic diagram of the composite film structure; b-slice SEM image of the composite film; c-EDS surface distribution map of C element; d-EDS surface distribution map of Co element; e-EDS surface distribution map of Ga element; f-EDS surface distribution map of Ti element; Figure 2 The images show scanning electron microscope (SEM) images of the top, middle and bottom layers of the G-BC / MXene / LM / C-Co thin film prepared in Example 1 of this invention. Figure 3 These are photographs of the top and bottom of the G-BC / MXene / LM / C-Co film prepared in Example 1 of this invention. Figure 4 The electromagnetic shielding performance of the composite films prepared in Examples 1 to 3 of this invention at frequencies of 8.2 to 12.4 GHz is shown in the figure. Figure 5 The image shows a comparison of the electromagnetic shielding performance (including reflection shielding effectiveness, absorption shielding effectiveness, and total electromagnetic shielding effectiveness) of the composite films prepared in Example 1 and Comparative Examples 1-3 of this invention at frequencies of 8.2~12.4GHz. Figure 6The graph shows the surface temperature of the G-BC / MXene / LM / C-Co thin film prepared in Example 1 of this invention as a function of time under a DC voltage of 2.5V. Figure 7 Infrared thermograms of the G-BC / MXene / LM / C-Co thin film prepared in Example 1 of this invention under different DC voltages; Figure 8 This is a graph showing the surface temperature of the G-BC / MXene / LM / C-Co thin film prepared in Example 1 of the present invention as a function of time under 2 Sun illumination. Figure 9 Infrared thermal images of the G-BC / MXene / LM / C-Co thin film prepared in Example 1 of this invention under 1.0 Sun and 2.0 Sun illumination; Figure 10 The stress-strain curve of the G-BC / MXene / LM / C-Co thin film prepared in Example 1 of this invention is shown. Figure 11 These are photographs of the load-bearing capacity and flexibility of the G-BC / MXene / LM / C-Co film prepared in Example 1 of this invention. Among them, a- is a physical photo of the load-bearing capacity of the composite film; b- is a physical photo of the flexibility of the composite film. Detailed Implementation
[0017] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0018] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0019] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0020] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0021] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0022] The purpose of this invention is to provide a low-reflection electromagnetic shielding film with an asymmetric gradient and its preparation method. This composite film effectively solves the problem of severe secondary electromagnetic wave reflection caused by impedance mismatch in highly conductive materials by constructing an asymmetric electromagnetic dual-gradient layered structure, while also endowing the film with excellent mechanical flexibility and Joule heating / photothermal conversion dual-mode thermal management functionality.
[0023] This invention provides a method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient, comprising the following steps: Step 1: Prepare Ti3C2T separately X MXene dispersion, carbon-coated cobalt nanospheres (C-Co), and liquid metal suspension (LM); Step 2: Dissolve bacterial cellulose (BC, 1% by mass) in deionized water and stir thoroughly for 1-2 hours to prepare a bacterial cellulose dispersion with a concentration of 1 mg / mL; add the C-Co nanospheres to the bacterial cellulose dispersion and stir thoroughly to obtain the top layer dispersion (BC / C-Co); add the LM suspension and C-Co nanospheres to the bacterial cellulose dispersion and stir thoroughly to obtain the middle layer dispersion (BC / LM / C-Co); add the Ti3C2T... X MXene dispersion and liquid metal suspension were added to bacterial cellulose dispersion and stirred thoroughly to obtain bottom dispersion (BC / MXene / LM). Step 3: Using a layer-by-layer vacuum-assisted filtration method, the BC / MXene / LM bottom layer dispersion, the BC / LM / C-Co intermediate layer dispersion, and the BC / C-Co top layer dispersion are sequentially filtered to form a film. The wet film is then vacuum-dried and hot-pressed to finally obtain the BC / MXene / LM / C-Co thin film. Preferably, in step 1, the Ti3C2T X The preparation process of MXene dispersion is as follows: Dissolve 1-2 g of lithium fluoride (LiF) in 20-40 mL of 9 mol / L hydrochloric acid (HCl) solution, then add 1-2 g of Ti3AlC2 powder and stir at 30-40 °C for 24-36 h for etching. Wash the resulting product repeatedly with deionized water and centrifuge until the pH of the supernatant is approximately 6. Collect the precipitate and sonicate it for 1-1.5 h, then centrifuge at 3600-4500 rpm for 0.5-1 h. Take the supernatant to obtain the Ti3C2T. X MXene dispersion.
[0024] Preferably, the preparation process of C-Co nanospheres in step 1 is as follows: Dissolve 2-10 mmol of adenine in 80-400 mL of N,N-dimethylformamide, heat to 140 °C, and then add dropwise 20-100 mL of N,N-dimethylformamide solution containing 1-5 mmol of cobalt nitrate hexahydrate. After reacting for 4 h, a precursor is obtained. The precursor is then carbonized at 600 °C for 1-2 h under an argon atmosphere to obtain C-Co nanospheres.
[0025] Preferably, the preparation process of suspension M in step 1 is as follows: Add 0.1~0.5g of eutectic gallium indium alloy to 10~50ml of anhydrous ethanol and ultrasonically disperse for 1h~2h. Centrifuge and redisperse the precipitate in deionized water to prepare an LM suspension with a concentration of 5mg / mL.
[0026] Preferably, the preparation process of the BC / C-Co top layer dispersion (top layer dispersion) in step 2 is as follows: Add 0.08~0.12g of the C-Co nanospheres to 50 mL of BC dispersion with a concentration of 1 mg / mL, sonicate for 30 min and stir for 2~3 h to obtain the top layer dispersion.
[0027] Preferably, in step 2, the mass ratio of C-Co nanospheres in the top layer dispersion to C-Co nanospheres in the middle layer dispersion is 2:1, so as to construct a magnetic gradient structure.
[0028] Preferably, the preparation process of the BC / LM / C-Co intermediate layer dispersion (intermediate layer dispersion) in step 2 is as follows: The mass ratio of C-Co nanospheres to LM is 1:1. C-Co nanospheres and LM suspension with a concentration of 5 mg / mL are added to 40 mL of BC dispersion with a concentration of 1 mg / mL. The mixture is sonicated for 30 min and stirred for 2-3 h to obtain the intermediate layer dispersion.
[0029] Preferably, in step 2, the mass ratio of C-Co nanospheres to LM in the intermediate layer dispersion is 1:1, that is, the amount of C-Co nanospheres is 0.04~0.06g, and the amount of LM suspension is 8~12mL.
[0030] Preferably, the preparation process of the BC / MXene / LM bottom layer dispersion (bottom layer dispersion) in step 2 is as follows: Ti3C2T X MXene dispersion and LM suspension with a concentration of 5 mg / mL were added sequentially to 30 mL of BC dispersion with a concentration of 1 mg / mL. After stirring for 2-3 h, the mixture was sonicated in an ice bath for 30 min to obtain the bottom dispersion.
[0031] Preferably, the Ti3C2T in the bottom dispersion X The mass ratio of MXene to liquid metal is (0.12~0.6):(1~1.2), i.e., Ti3C2T X The dosage of MXene is 0.012~0.06g, and the dosage of liquid metal suspension is 20~24mL.
[0032] Preferably, in step 3, the filter membrane used for vacuum-assisted filtration is a polytetrafluoroethylene microporous filter membrane (pore size 0.45 micrometers); the vacuum drying temperature for the wet membrane is 40~60℃, and the time is 4~8h; the hot pressing temperature is 40℃, the pressure is 5kPa, and the time is 0.5~1h, finally obtaining a BC / MXene / LM / C-Co film (a low-reflection electromagnetic shielding film with an asymmetric gradient). In this invention, Ti3C2T X Ti3C2T in MXene dispersion X It is a type of Mxene, where Tx represents the functional groups on its surface, such as -OH, -F, -O, etc.
[0033] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0034] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0035] Example 1 A method for preparing a low-reflection electromagnetic shielding thin film (G-BC / MXene / LM / C-Co thin film) with an asymmetric gradient includes the following steps: Step 1: Prepare Ti3C2T separately X MXene dispersion, carbon-coated cobalt nanospheres (C-Co), and liquid metal suspension (LM); The Ti3C2T X The preparation process of MXene dispersion is as follows: 2g of lithium fluoride was dissolved in 40mL of 9mol / L hydrochloric acid solution, followed by the addition of 2g of Ti3AlC2 powder. The mixture was stirred at 35℃ for 24h for etching. The resulting product was repeatedly washed with deionized water and centrifuged until the pH of the supernatant was approximately 6. The precipitate was collected and ultrasonically exfoliated for 1h, then centrifuged at 3600rpm for 1h. The supernatant was collected to obtain Ti3C2T. X MXene dispersion; The preparation process of the C-Co nanospheres is as follows: 10 mmol adenine was dissolved in 400 mL N,N-dimethylformamide (DMF), heated to 140 °C, and then 100 mL DMF solution containing 5 mmol cobalt nitrate hexahydrate was added dropwise. After reacting for 4 h, the precipitate was collected, washed and dried to obtain the precursor. The precursor was carbonized at 600 °C for 1 h under an argon atmosphere to obtain C-Co nanospheres. The preparation process of the LM suspension is as follows: 0.2 g of eutectic gallium indium alloy was added to 20 mL of anhydrous ethanol and ultrasonically dispersed for 1 h. The precipitate was centrifuged and redispersed in deionized water to prepare an LM suspension with a concentration of 5 mg / mL. Step 2: Dissolve bacterial cellulose (BC, 1% by mass) in deionized water and stir thoroughly for 1 hour to prepare a bacterial cellulose dispersion with a concentration of 1 mg / mL; prepare the top layer dispersion (BC / C-Co), the middle layer dispersion (BC / LM / C-Co), and the bottom layer dispersion (BC / MXene / LM) separately. The preparation process of the top layer dispersion is as follows: 0.1 g of C-Co nanospheres were added to 50 mL of BC dispersion (1 mg / mL, mass fraction 1%), ultrasonically dispersed for 30 min and stirred for 2 h to obtain the top layer dispersion (BC / C-Co). The preparation process of the intermediate layer dispersion is as follows: 0.05 g of C-Co nanospheres and 10 mL of the LM suspension with a concentration of 5 mg / mL (i.e., LM mass is 0.05 g, and the mass ratio of C-Co to LM is 1:1) were added to 40 mL of BC dispersion with a concentration of 1 mg / mL. The mixture was sonicated and stirred for 2 h to obtain an intermediate layer dispersion (BC / LM / C-Co). The preparation process of the bottom dispersion is as follows: Ti3C2T X MXene dispersion (MXene solid content of 0.06 g) and 20 mL of the LM suspension with a concentration of 5 mg / mL (i.e., LM mass of 0.1 g) were added sequentially to 30 mL of BC dispersion with a concentration of 1 mg / mL. After stirring for 2 h, the mixture was sonicated in an ice bath for 30 min to obtain the bottom dispersion (BC / MXene / LM). Step 3: Using a layer-by-layer vacuum-assisted filtration method, a polytetrafluoroethylene microporous filter membrane with a pore size of 0.45 micrometers is used to sequentially filter the BC / MXene / LM bottom layer dispersion, the BC / LM / C-Co intermediate layer dispersion, and the BC / C-Co top layer dispersion to form a film. The wet film is then vacuum dried at 40°C for 6 h, followed by hot pressing at 40°C and 5 kPa pressure for 1 h to finally obtain a G-BC / MXene / LM / C-Co film with an asymmetric gradient.
[0036] Example 2 A method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient includes the following steps: Step 1: The basic operation of preparing the BC / MXene / LM / C-Co electromagnetic shielding film in Step 1 of this embodiment is basically the same as that in Step 1 of Embodiment 1, and will not be repeated here.
[0037] Step 2: The basic operation for preparing the BC / MXene / LM / C-Co electromagnetic shielding film in step 2 of this embodiment is basically the same as that in step 2 of embodiment 1, except that: The preparation process of the bottom dispersion is as follows: Ti3C2T XMXene dispersion (MXene solid content of 0.036 g) and 20 mL of the LM suspension with a concentration of 5 mg / mL (i.e., LM mass of 0.1 g) were sequentially added to 30 mL of BC dispersion with a concentration of 1 mg / mL. After stirring for 2 h, the mixture was sonicated in an ice bath for 30 min to obtain the bottom dispersion (BC / MXene / LM). The remaining processes are basically the same and will not be described in detail here. Step 3: Using a layer-by-layer vacuum-assisted filtration method, a polytetrafluoroethylene microporous filter membrane with a pore size of 0.45 micrometers is used to sequentially filter the BC / MXene / LM bottom layer dispersion, the BC / LM / C-Co intermediate layer dispersion, and the BC / C-Co top layer dispersion to form a film. The wet film is then vacuum dried at 40°C for 6 h, followed by hot pressing at 40°C and 5 kPa pressure for 1 h to finally obtain a BC / MXene / LM / C-Co film with an asymmetric gradient.
[0038] Example 3 A method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient includes the following steps: Step 1: The basic operation of preparing the BC / MXene / LM / C-Co electromagnetic shielding film in Step 1 of this embodiment is basically the same as that in Step 1 of Embodiment 1, and will not be repeated here.
[0039] Step 2: The basic operation for preparing the BC / MXene / LM / C-Co electromagnetic shielding film in step 2 of this embodiment is basically the same as that in step 2 of embodiment 1, except that: The preparation process of the bottom dispersion is as follows: Ti3C2T X MXene dispersion (MXene solid content of 0.012 g) and 20 mL of the LM suspension with a concentration of 5 mg / mL (i.e., LM mass of 0.1 g) were sequentially added to 30 mL of BC dispersion with a concentration of 1 mg / mL. After stirring for 2 h, the mixture was sonicated in an ice bath for 30 min to obtain the bottom dispersion (BC / MXene / LM). The remaining processes are basically the same and will not be described in detail here. Step 3: Using a layer-by-layer vacuum-assisted filtration method, a polytetrafluoroethylene microporous filter membrane with a pore size of 0.45 micrometers was used to sequentially filter the BC / MXene / LM bottom layer dispersion, the BC / LM / C-Co intermediate layer dispersion, and the BC / C-Co top layer dispersion to form a film. The wet film was then vacuum dried at 40℃ for 6 h, followed by hot pressing at 40℃ and 5 kPa pressure for 1 h to finally obtain a G-BC / MXene / LM / C-Co film with an asymmetric gradient.
[0040] Comparative Example 1: This comparative example provides a method for preparing a G-BC / MXene / LM electromagnetic shielding film with an asymmetric gradient. Compared to the method for preparing a G-BC / MXene / LM / C-Co electromagnetic shielding film with an asymmetric gradient described in Example 1, the difference lies in the fact that, as a control example, carbon-coated cobalt nanospheres were not introduced. Other operations are essentially the same, and the film is prepared through the following steps: Step 1: Prepare Ti3C2T separately X MXene dispersions and liquid metal suspensions (LM).
[0041] Specifically, the Ti3C2T X The preparation process of MXene dispersion is as follows: 2g of lithium fluoride was dissolved in 40mL of 9mol / L hydrochloric acid solution, followed by the addition of 2g of Ti3AlC2 powder. The mixture was stirred at 35℃ for 24h for etching. The resulting product was repeatedly washed with deionized water and centrifuged until the pH of the supernatant was approximately 6. The precipitate was collected and ultrasonically exfoliated for 1h, then centrifuged at 3600rpm for 1h. The supernatant was collected to obtain Ti3C2T. X MXene dispersion; Specifically, the preparation process of the LM suspension is as follows: 0.2 g of eutectic gallium indium alloy was added to 20 mL of anhydrous ethanol and ultrasonically dispersed for 1 h. The precipitate was centrifuged and redispersed in deionized water to prepare the LM suspension with a concentration of 5 mg / mL.
[0042] Step 2: Dissolve bacterial cellulose (BC, 1% by mass) in deionized water and stir thoroughly for 1 hour to prepare a bacterial cellulose dispersion with a concentration of 1 mg / mL; prepare the top layer dispersion BC, the middle layer dispersion (BC / LM) and the bottom layer dispersion (BC / MXene / LM) separately. Specifically, the preparation process of the top layer dispersion is as follows: Take 50 mL of BC dispersion with a concentration of 1 mg / mL and stir thoroughly for 2 h to use as the top layer dispersion; Specifically, the preparation process of the intermediate layer dispersion is as follows: 10 mL of LM suspension with a concentration of 5 mg / mL (i.e., LM mass of 0.05 g) was added to 40 mL of BC dispersion with a concentration of 1 mg / mL, and the mixture was sonicated for 30 min and stirred for 2 h to obtain the intermediate layer dispersion (BC / LM). Specifically, the preparation process of the bottom dispersion is as follows: Ti3C2T XMXene dispersion (MXene solid content of 0.06 g) and 20 mL of the LM suspension with a concentration of 5 mg / mL (i.e., LM mass of 0.1 g) were added sequentially to 30 mL of BC dispersion with a concentration of 1 mg / mL. After stirring for 2 h, the mixture was sonicated in an ice bath for 30 min to obtain the bottom dispersion (BC / MXene / LM). Step 3: Using a layer-by-layer vacuum-assisted filtration method, a polytetrafluoroethylene microporous filter membrane with a pore size of 0.45 micrometers was used to sequentially filter the BC / MXene / LM bottom layer dispersion, the BC / LM middle layer dispersion, and the BC top layer dispersion to form a film. The wet film was then vacuum dried at 40℃ for 6 h, followed by hot pressing at 40℃ and 5 kPa pressure for 1 h to finally obtain a G-BC / MXene / LM film with an asymmetric gradient.
[0043] Comparative Example 2 This comparative example provides a method for preparing a G-BC / MXene / C-Co electromagnetic shielding film with an asymmetric gradient. Compared to the method for preparing a G-BC / MXene / LM / C-Co electromagnetic shielding film with an asymmetric gradient described in Example 1, the difference lies in the fact that, as a control example, no liquid metal is introduced; other operations are essentially the same, and the film is prepared through the following steps: Step 1: Prepare Ti3C2T separately X MXene dispersion and carbon-coated cobalt nanospheres (C-Co).
[0044] Specifically, the Ti3C2T X The preparation process of MXene dispersion is as follows: 2g of lithium fluoride was dissolved in 40mL of 9mol / L hydrochloric acid solution, followed by the addition of 2g of Ti3AlC2 powder. The mixture was stirred at 35℃ for 24h for etching. The resulting product was repeatedly washed with deionized water and centrifuged until the pH of the supernatant was approximately 6. The precipitate was collected and ultrasonically exfoliated for 1h, then centrifuged at 3600rpm for 1h. The supernatant was collected to obtain Ti3C2T. X MXene dispersion; Specifically, the preparation process of the C-Co nanospheres is as follows: 10 mmol adenine was dissolved in 400 mL N,N-dimethylformamide (DMF), heated to 140 °C, and then 100 mL DMF solution containing 5 mmol cobalt nitrate hexahydrate was added dropwise. After reacting for 4 h, the precipitate was collected, washed and dried to obtain the precursor. The precursor was carbonized at 600 °C for 1 h under an argon atmosphere to obtain C-Co nanospheres. Step 2: Dissolve bacterial cellulose (BC, 1% by mass) in deionized water and stir thoroughly for 1 hour to prepare a bacterial cellulose dispersion with a concentration of 1 mg / mL; prepare the top layer dispersion, the middle layer dispersion, and the bottom layer dispersion (BC / MXene) separately. Specifically, the preparation process of the top layer dispersion is as follows: 0.1 g of the C-Co nanospheres were added to 50 mL of BC dispersion with a concentration of 1 mg / mL (mass fraction 1%), ultrasonically dispersed for 30 min and stirred for 2 h to obtain the top layer dispersion; Specifically, the preparation process of the intermediate layer dispersion is as follows: 0.05 g of the C-Co nanospheres were added to 40 mL of BC dispersion with a concentration of 1 mg / mL, and the mixture was sonicated and stirred for 2 h to obtain an intermediate layer dispersion. Specifically, the preparation process of the bottom dispersion is as follows: Ti3C2T X MXene dispersion (MXene solid content of 0.06 g) was added to 30 mL of BC dispersion with a concentration of 1 mg / mL, stirred for 2 h, and then sonicated in an ice bath for 30 min to obtain the bottom dispersion. Step 3: Using a layer-by-layer vacuum-assisted filtration method, a polytetrafluoroethylene microporous filter membrane with a pore size of 0.45 micrometers was used to filter the bottom layer dispersion, the middle layer dispersion, and the top layer dispersion in sequence to form a film. The wet film was then vacuum dried at 40°C for 6 h, followed by hot pressing at 40°C and 5 kPa for 1 h to finally obtain a G-BC / MXene / C-Co film with an asymmetric gradient.
[0045] Comparative Example 3: This comparative example provides a method for preparing a G-BC / LM / C-Co electromagnetic shielding film with an asymmetric gradient. The difference between this method and the method described in Example 1, which also has an asymmetric gradient, is that Ti3C2T is not introduced as a control example. X MXene is prepared through the following steps, with other operations being basically the same: Step 1: Prepare carbon-coated cobalt nanospheres (C-Co) and liquid metal suspension (LM) respectively.
[0046] Specifically, the preparation process of the C-Co nanospheres is as follows: 10 mmol adenine was dissolved in 400 mL N,N-dimethylformamide (DMF), heated to 140 °C, and then 100 mL DMF solution containing 5 mmol cobalt nitrate hexahydrate was added dropwise. After reacting for 4 h, the precipitate was collected, washed, and dried to obtain the precursor. The precursor was carbonized at 600 °C for 1 h under an argon atmosphere to obtain C-Co nanospheres. Specifically, the preparation process of the LM suspension is as follows: 0.2 g of eutectic gallium indium alloy was added to 20 mL of anhydrous ethanol and ultrasonically dispersed for 1 h. The precipitate was centrifuged and redispersed in deionized water to prepare the LM suspension with a concentration of 5 mg / mL. Step 2: Dissolve bacterial cellulose (BC, 1% by mass) in deionized water and stir thoroughly for 1 hour to prepare a bacterial cellulose dispersion with a concentration of 1 mg / mL; prepare the top layer dispersion (BC / C-Co), the middle layer dispersion (BC / LM / C-Co), and the bottom layer dispersion (BC / LM) separately. Specifically, the preparation process of the top layer dispersion is as follows: 0.1 g of the C-Co nanospheres were added to 50 mL of BC dispersion (1 mg / mL, mass fraction 1%), ultrasonically dispersed for 30 min and stirred for 2 h to obtain the top layer dispersion (BC / C-Co). Specifically, the preparation process of the intermediate layer dispersion is as follows: 0.05 g of the C-Co nanospheres and 10 mL of the LM suspension with a concentration of 5 mg / mL (i.e., LM mass is 0.05 g, and the mass ratio of C-Co to LM is 1:1) were added to 40 mL of BC dispersion with a concentration of 1 mg / mL. The mixture was sonicated and stirred for 2 h to obtain an intermediate layer dispersion (BC / LM / C-Co). Specifically, the preparation process of the bottom dispersion is as follows: 20 mL of the LM suspension with a concentration of 5 mg / mL (i.e., LM mass of 0.1 g) was added to 30 mL of BC dispersion with a concentration of 1 mg / mL. After stirring for 2 h, the mixture was sonicated in an ice bath for 30 min to obtain the bottom dispersion (BC / LM). Step 3: Using a layer-by-layer vacuum-assisted filtration method, a polytetrafluoroethylene microporous filter membrane with a pore size of 0.45 micrometers is used to sequentially filter the BC / LM bottom layer dispersion, the BC / LM / C-Co intermediate layer dispersion, and the BC / C-Co top layer dispersion to form a film. The wet film is then vacuum dried at 40°C for 6 h, followed by hot pressing at 40°C and 5 kPa pressure for 1 h to finally obtain a G-BC / LM / C-Co film with an asymmetric gradient.
[0047] Experimental Example 1: The G-BC / MXene / LM / C-Co electromagnetic shielding film prepared in Example 1 was characterized by scanning electron microscopy (SEM) of its cross-section. The resulting microscopic images are shown below. Figure 1 and Figure 2 .
[0048] Figure 1 This image shows a schematic diagram, cross-sectional scanning electron microscope (SEM) image, and EDS elemental mapping image of the G-BC / MXene / LM / C-Co thin film prepared in Example 1 of this invention. Figure 1 As shown in the structural diagram in (a), this invention designs a top layer (BC / C-Co) enriched with magnetic carbon-coated cobalt nanospheres (C-Co) to optimize impedance matching, a middle layer (BC / LM / C-Co) synergistically combining C-Co nanospheres and liquid metal (LM) to dissipate electromagnetic waves, and a bottom layer enriched with Ti3C2T. X MXene and LM are used to construct an asymmetric electromagnetic dual-gradient structure for a reflective barrier. Figure 1 (b) The cross-sectional scanning electron microscope image shows that the film has a dense layered structure with a total thickness of approximately 270 µm, and no obvious stratification was observed between adjacent layers, which is mainly attributed to the interaction between the bacterial cellulose networks. Further analysis... Figure 1 (c) to Figure 1 As shown in the EDS elemental mapping diagram in (f), the key elements exhibit a gradually changing complementary distribution: Ti is mainly concentrated in the bottom region, while Ga is most abundant in the bottom region and gradually decreases upwards; conversely, Co is most abundant in the top region and gradually decreases downwards. This spatial gradient directly confirms the successful construction of the asymmetric electromagnetic double gradient structure.
[0049] Depend on Figure 2 Scanning electron microscopy (SEM) images show that abundant C-Co nanospheres are uniformly embedded in a porous bacterial cellulose network in the top layer of the film. This porous magnetic structure facilitates impedance matching with free space, allowing electromagnetic waves to penetrate the film interior rather than being directly reflected at the surface. The distribution density of C-Co nanospheres in the middle layer is significantly lower than that in the top layer, indicating that the magnetic component gradually decreases towards the interior. The bottom layer exhibits a composition of Ti3C2T... X The dense layered structure formed by the tight bonding of MXene nanosheets and bacterial cellulose nanofibers is similar to a typical "brick-and-mortar" structure. This highly conductive and dense bottom layer can serve as an efficient reflection barrier, inducing multiple reflections and reabsorptions of electromagnetic waves, thereby achieving efficient shielding.
[0050] Figure 3 Photographs of the top and bottom of the composite film prepared in Example 1 are provided. As can be seen from the figures, the top of the film is black, while the bottom has a metallic luster. This macroscopic color difference intuitively reflects the asymmetric structural characteristics of the composite film.
[0051] Figure 4 Electromagnetic shielding performance diagrams of the composite films prepared in Examples 1-3 at frequencies ranging from 8.2 to 12.4 GHz are presented. From the diagrams, it can be seen that with the underlying Ti3C2T... X The increase in MXene content significantly improves the overall shielding effectiveness. In Example 1, the overall shielding effectiveness can reach up to 63.65 dB, which meets the requirements of commercial electromagnetic shielding materials.
[0052] Figure 5 Comparison graphs of the electromagnetic shielding performance of the composite films prepared in Example 1 and Comparative Examples 1 to 3 at frequencies ranging from 8.2 to 12.4 GHz are provided. From the graphs, it can be seen that Example 1, while possessing an excellent total shielding effectiveness of 63.65 dB, exhibits a low reflection shielding effectiveness (SE). R The absorption shielding effectiveness (SE) is only 8.05 dB. A The shielding efficiency reached 55.60 dB, effectively preventing secondary electromagnetic pollution. Comparative Example 1 (without C-Co) showed a significant increase in reflection efficiency to 12.69 dB due to the lack of magnetic components to adjust impedance matching; Comparative Example 2 (without liquid metal) showed a decrease in overall shielding efficiency, demonstrating that liquid metal contributes to improving the overall conductive network; Comparative Example 3 (without Ti3C2T) X The overall shielding effectiveness of MXene is extremely low, proving that Ti3C2T X MXene is an indispensable conductive framework for constructing shielding networks. This demonstrates that synergistic design of components and asymmetric gradient design are key to achieving "high shielding and low reflection".
[0053] Figure 6 The surface temperature curve of the composite film prepared in Example 1 as a function of time under a DC voltage of 2.5V is presented. As can be seen from the figure, after applying a voltage of 2.5V, the surface temperature of the film rises rapidly over time and tends to stabilize, with the highest surface temperature reaching 121.9 °C, demonstrating excellent low-voltage driven Joule heating performance.
[0054] Figure 7 Infrared thermographic images of the composite film prepared in Example 1 under different DC voltages are presented. It can be clearly observed from the images that as the applied voltage increases, the red area (high-temperature area) on the film surface is uniformly distributed and the temperature increases significantly, demonstrating the excellent and uniform electrothermal conversion performance of the film.
[0055] Figure 8 The surface temperature curve of the composite film prepared in Example 1 under 2 Sun illumination over time is shown. As can be seen from the figure, the surface temperature of the film rapidly rises to 80.0 °C within 30 s, demonstrating its efficient photothermal conversion capability.
[0056] Figure 9Infrared thermographic images of the composite film prepared in Example 1 under 1.0 Sun and 2.0 Sun illumination are presented. As can be seen from the images, the surface temperature of the film increases rapidly with increasing light intensity, and the heat distribution is uniform, further confirming its efficient and stable photothermal conversion capability.
[0057] Figure 10 The stress-strain curves of the composite film prepared in Example 1 are presented. The figure shows that the maximum tensile stress reaches 35.47 MPa. This is attributed to the use of bacterial cellulose as a flexible framework spanning the three layers, combined with the fluid properties of liquid metal, which endows the film with excellent mechanical flexibility, meeting the application requirements of flexible wearable devices.
[0058] Figure 11 Photographs of the composite film prepared in Example 1 demonstrate its load-bearing capacity and flexibility. As shown in the figures, the lightweight film successfully supports a 200 g weight without breaking, proving its excellent load-bearing capacity. Furthermore, the film maintains good structural integrity under bending conditions, without breakage or cracking, indicating its outstanding flexibility, which meets the application requirements of flexible wearable devices.
[0059] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient, characterized in that, Includes the following steps: S1: Carbon-coated cobalt nanospheres were added to the bacterial cellulose dispersion and stirred to obtain the top layer dispersion; S2: Liquid metal suspension and carbon-coated cobalt nanospheres are added to bacterial cellulose dispersion and stirred to obtain intermediate layer dispersion; S3: Ti3C2T X MXene dispersion and liquid metal suspension were added sequentially to bacterial cellulose dispersion, and the mixture was stirred to obtain the bottom dispersion. S4: The top layer dispersion, the middle layer dispersion and the bottom layer dispersion are sequentially filtered to form a film, and the top layer film, the middle layer film and the bottom layer film are obtained in sequence; the top layer film, the middle layer film and the bottom layer film are sequentially stacked, dried and hot-pressed to obtain a low-reflection electromagnetic shielding film with an asymmetric gradient.
2. The method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient according to claim 1, characterized in that, In S1, the preparation process of the carbon-coated cobalt nanospheres is as follows: Dissolve 2-10 mmol adenine in 80-400 mL N,N-dimethylformamide, heat to 140 °C, and then add dropwise 20-100 mL N,N-dimethylformamide solution containing 1-5 mmol cobalt nitrate hexahydrate. After reacting for 4 h, a precursor is obtained. The precursor is then carbonized at 600 °C for 1-2 h under an argon atmosphere to obtain carbon-coated cobalt nanospheres. The preparation process of the top layer dispersion is as follows: Add 0.08~0.12g of the carbon-coated cobalt nanospheres to 50 mL of bacterial cellulose dispersion with a concentration of 1 mg / mL, sonicate for 30 min and stir for 2~3 h to obtain the top layer dispersion.
3. The method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient according to claim 1, characterized in that, In S2 and S3, the preparation process of the liquid metal suspension is as follows: Add 0.1~0.5g of eutectic gallium-indium alloy to 10~50mL of anhydrous ethanol and ultrasonically disperse for 1h~2h. Centrifuge and redisperse the precipitate in deionized water to prepare a liquid metal suspension with a concentration of 5mg / mL.
4. The method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient according to claim 1, characterized in that, In S2, the ratio of the C-Co nanospheres to the liquid metal suspension is 0.04~0.06g:8~12mL; The specific preparation process of the intermediate layer dispersion is as follows: C-Co nanospheres and a liquid metal suspension with a concentration of 5 mg / mL were added to 40 mL of bacterial cellulose dispersion with a concentration of 1 mg / mL. The mixture was sonicated for 30 min and stirred for 2-3 h to obtain an intermediate layer dispersion.
5. The method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient according to claim 1, characterized in that, In S3, Ti3C2T X The preparation method of MXene dispersion is as follows: Dissolve 1-2 g of lithium fluoride in 20-40 mL of 9 mol / L hydrochloric acid solution, then add 1-2 g of Ti3AlC2 powder and stir at 30-40 °C for 24-36 h for etching. Wash the resulting product repeatedly with deionized water and centrifuge until the pH of the supernatant is approximately 6. Collect the precipitate and sonicate it for 1-1.5 h, then centrifuge at 3600-4500 rpm for 0.5-1 h. Take the supernatant to obtain Ti3C2T. X MXene dispersion.
6. The method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient according to claim 1, characterized in that, In S3, the preparation method of the bottom dispersion is as follows: Ti3C2T X MXene dispersion and a liquid metal suspension with a concentration of 5 mg / mL were added sequentially to 30 mL of bacterial cellulose dispersion with a concentration of 1 mg / mL. After stirring for 2-3 h, the mixture was sonicated in an ice bath for 30 min to obtain the bottom dispersion.
7. The method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient according to claim 6, characterized in that, In S3, the Ti3C2T in the bottom dispersion X The ratio of MXene to liquid metal suspension is 0.012~0.06g: 20~24mL.
8. The method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient according to claim 1, characterized in that, In S1~S3, the preparation process of the bacterial cellulose dispersion is as follows: dissolve bacterial cellulose in deionized water and stir thoroughly for 1~2 hours to obtain the bacterial cellulose dispersion.
9. The method for preparing a low-reflection electromagnetic shielding film with an asymmetric gradient according to claim 1, characterized in that, The mass ratio of carbon-coated cobalt nanospheres in the top layer dispersion to that in the middle layer dispersion is 2:1; In S3, the filtration membrane formation is performed using vacuum-assisted filtration; the filter membrane used in the vacuum-assisted filtration is a polytetrafluoroethylene microporous filter membrane; the drying is vacuum drying, the temperature of the vacuum drying is 40~60℃, and the time is 4~8h; the hot pressing temperature is 40℃, the pressure is 5kPa, and the time is 0.5~1h.
10. A low-reflection electromagnetic shielding film with an asymmetric gradient, characterized in that, The asymmetric gradient of the low-reflection electromagnetic shielding film is as follows: along the thickness direction of the film, from the top layer to the bottom layer, the content of the magnetic component, carbon-coated cobalt nanospheres, gradually decreases, while the content of the conductive component, Ti3C2T... X The content of MXene and liquid metal gradually increases, forming a functional gradient distribution with the top layer dominated by magnetic loss, the middle layer having both magnetic and dielectric loss, and the bottom layer dominated by dielectric loss.